We can start by saying that 4/3w+ 3/3w = 133.
we can simplify to 7/3w = 133.
multiply both sides by 3 to get 7w = 399.
divide both sides by 7 to get 57.
Mr. Wong's mass is 57 kg.
The answer is y=-3
This is here for the 20 characters
Answer:
The expressions are not equivalent because -3(2)(5-4)+3(2-6)=-18 and -12(2)-6=-30
Step-by-step explanation:
Two expressions are said to be equal if after a number is substituted to the expression, they produce the same result (that is they have the same value).
To determine whether -3x(5-4)+3(x-6) is equivalent to -12x-6, we have to substitute the same number to the expression and see if it produces the same result.
Substituting 2 to the first expression gives:
-3×2(5-4) + 3(2 - 6) = -6 - 12 = -18
Substituting 2 to the second expression gives:
-12(2) - 6 = -24 - 6 = -30
Since -3×2(5-4) + 3(2 - 6) = -6 - 12 = -18 and -12(2) - 6 = -24 - 6 = -30, the expressions are not equivalent because they do not produce the same result.